2004
DOI: 10.1099/vir.0.19394-0
|View full text |Cite
|
Sign up to set email alerts
|

Delay in onset of prion disease for the HY strain of transmissible mink encephalopathy as a result of prior peripheral inoculation with the replication-deficient DY strain

Abstract: We report that the replication-deficient DY strain of transmissible mink encephalopathy (TME) can delay disease caused by the pathogenic HY TME strain. In this study, competition between the HY and DY TME agents was investigated following superinfection of the sciatic nerve and peritoneal cavity. Initially, DY TME infection was examined in the absence of superinfection and it was found that inoculation into the brain and sciatic nerve resulted in prion disease and PrP Sc deposition in brain but not lymphoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 27 publications
4
57
1
Order By: Relevance
“…A 60 or 90 day interval between DY TME agent infection and HY TME agent superinfection resulted in all of the animals developing clinical signs of HY TME with Per os prion strain interference www.landesbioscience.com Prionnodes, which is the major site of extraneural HY TME agent replication. 11,21,26 The DY TME agent can interfere with the HY TME agent following intraperitoneal and per os infection, suggesting that the DY TME agent is replicating in other locations that are involved in HY TME agent neuroinvasion (Table 2). 11 Table 2 Clinical signs and incubation periods of hamsters per os inoculated with either the HY TME or DY TME agent, or per os co-infected with the DY TME agent 60, 90 or 120 days prior to superinfection of hamsters with the HY TME agent …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A 60 or 90 day interval between DY TME agent infection and HY TME agent superinfection resulted in all of the animals developing clinical signs of HY TME with Per os prion strain interference www.landesbioscience.com Prionnodes, which is the major site of extraneural HY TME agent replication. 11,21,26 The DY TME agent can interfere with the HY TME agent following intraperitoneal and per os infection, suggesting that the DY TME agent is replicating in other locations that are involved in HY TME agent neuroinvasion (Table 2). 11 Table 2 Clinical signs and incubation periods of hamsters per os inoculated with either the HY TME or DY TME agent, or per os co-infected with the DY TME agent 60, 90 or 120 days prior to superinfection of hamsters with the HY TME agent …”
mentioning
confidence: 99%
“…10 Interference between other prion strains has been described in mice and hamsters using rodent-adapted strains of scrapie, TME, Creutzfeldt-Jacob disease and Gerstmannn-Sträussler-Scheinker syndrome following intracerebral, intraperitoneal, intravenous and sciatic nerve routes of inoculation. [10][11][12][13][14][15] We previously demonstrated the detection of PrP Sc from the long incubation period DY TME agent correlated with its ability to extend the incubation period or completely block the superinfecting short incubation period HY TME agent from causing disease and results in a reduction of HY PrP Sc levels following sciatic nerve inoculation. 12 However, it is not known if a single long incubation period agent (e.g., DY TME) can interfere with more than one short incubation period agent or if interference can occur by a natural route of infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prion interference has been observed in vivo in mice and Syrian hamsters that were inoculated simultaneously or sequentially with two distinct strains of prions. [55][56][57][58] Since we observed no direct interaction between different conformers of PrP Sc in our in vitro mixing experiments with "pure" MM1 and MM2 sCJD prions, we concluded that the most likely explanation is competition for PrP C substrate or auxiliary molecule; however, the exact molecular mechanism of this phenomenon remains to be fully elucidated. 34 Cumulatively, the distinct particle size, conformational stability, and amplification rate of these prion subtypes argue for the frequent coexistence of different sCJD prions in the same host (Fig.…”
Section: 54mentioning
confidence: 66%
“…137 In addition to positive interactions between prions, co-existence of multiple prion forms, whether they are different sequences or different variants of the same sequence, is often disfavored. For example, co-inoculation of mice with distinct PrP variants extends incubation timing; 138,139 140 These observations suggest a competition for some component common to the propagation pathways. One example of this idea is the competition between different variants of the same prion protein.…”
Section: Modulating Prion Dynamicsmentioning
confidence: 99%